The social, professional, economic and institutional recognition of the nursing profession: results of a survey among Italian nurses (Dissertation Nursing, 2023)
INTRODUCTION: The crisis of the nursing profession in Italy is real on a social, professional, economic, and institutional level. It seems that the current problems largely mirror those present in Italy more than a hundred years ago.METHODS: An online cross-sectional survey was conducted from 23 December 2022 to 23 January 2023. Nurses were asked to rate on a Likert scale from 1 (lowest) to 10 (highest) their agreement with the 20 statements in the questionnaire, referring to the general Italian nursing context. The content of the statements corresponded to some problems present in the Italian nursing context at the turn of the century between 1800 and 1900.RESULTS: 477 nurses participated in the survey. The instrument proved to be valid and reliable: the exploratory factor analysis showed loadings above the Stevens cutoff highlighting the existence of the seven domains envisaged when the instrument was constructed. The internal consistency was satisfactory (global omega=0.894). DISCUSSION/CONCLUSION: After one hundred years, institutional interventions in the direction of a European and global modernization of the profession are still awaited. It is true that nurses professional autonomy, which several European states were already building at the dawn of the 1900s, was only celebrated in our country in the last decade of the previous century, but we are not in a position to wait another century for concrete intervention. Professional neglect has already reaped its victims to a large extent, and without nurses, the Italian healthcare system is at risk.
Keywords: Nurses; Recognition; Skills; Salary; Issues